The urban edge : a spatial planning tool or device for land development management : a Western Cape perspective - Wylie, Diana (Institute of Marine and Environmental Law, 2016)
The regulation of South African land use planning law is challenging; it is a field that is complex and not fully understood.1 One reason for the complexity in the past was the number of laws that were in force.2 Other factors include the number of authorities that are involved, the irregular implementation of the land use planning tools and the gap that is prevalent generally between planning theory and practise.34 The assortment of laws is implemented by authorities using land use planning tools.5 An array of land use planning tools, such as zoning and urban edge boundaries, are used in the planning process to distinguish the various aspects of development from one another. The combined English and Roman Dutch sources of our planning law passed down traditional land use planning devices such as: zoning schemes, subdivision and title deed restrictions.6 A range of unique South African tools, such as; guide plans, regional plans and urban structure plans were used for regional planning during apartheid times.7 Several new planning tools have been created since 1994 to give effect to changing policy, such as; land development objectives, environmental impact assessments (EIAs), integrated development plans (IDPs), spatial development frameworks (SDFs), the designation of different types of protected areas; urban edge lines and marine set back delineations.8 This thesis will analyse the status of the urban edge as a land use planning tool.